ANALYSIS OF THE EFFECT OF PRICE, PRODUCT QUALITY AND BRAND IMAGE ON THE PURCHASE DECISION OF PT SEMEN INDONESIA (PERSERO) TBK PRODUCTS WITH THE SEMEN ANDALAS BRAND IN MEDAN CITY - Doan Carlo Trimora; Arlina Nurbaity Lubis; Nismah Panjaitan (Journal Analytica Islamica, 2025)
This study investigates how price, product quality, and brand image shape retailers' purchase decisions for Semen Andalas, a product of PT Semen Indonesia (Persero) Tbk, in Medan City. The research is motivated by a paradoxical market phenomenon: regional cement demand and overall corporate sales are increasing, yet Semen Andalas is experiencing a declining market share amid intensifying competition. Adopting a causal research design, the study surveys all 97 building-material stores in Medan that have purchased Semen Andalas, using saturated sampling. Price, product quality, brand image, and purchase decision are operationalized into multi-item Likert scales, whose validity and reliability are confirmed through Pearson product-moment correlations and Cronbach's alpha. Data are analyzed using descriptive statistics, classical assumption tests, and multiple linear regression. The results show that price, product quality, and brand image jointly explain 49.3% of the variance in purchase decisions (R² = 0.493) and have a positive and significant simultaneous effect. Partially, each variable also exerts a positive and significant influence, with price emerging as the strongest predictor, followed by product quality and brand image. These findings indicate that retailers' decisions are driven by a combination of perceived price fairness, functional performance, and brand trust rather than by product attributes alone. The study underscores the need for an integrated strategy that aligns pricing, quality management, and brand-building initiatives to strengthen Semen Andalas' competitive position in Medan's cement market.